PENINGKATAN HASIL BELAJAR IPS SISWA DENGAN MENGGUNAKAN METODE LATIHAN DI KELAS IV SD NEGERI 006 TRI MULYA JAYA KECAMATAN UKUI - Ngadimin ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is a classroom action research is motivated by the low learning outcomes IPSfourth grade students SD Negeri 006 Tri Mulya Jaya Kecamatan Ukui. This study wasconducted by two cycles by applying the method of exercise. The data used in this study is theteacher and student activity data and the results of social studies students. The study statesthat the activities of teachers and students and learning outcomes IPS has increased after theaction, this is evidenced by: (a) the activities of teachers has increased, in the first cycle ofactivity for teachers to get a score of 19 (63.00%) with a category (quite perfect ). In thesecond cycle increased with the acquisition of a score of 22 (73.00%) with a category(perfect); (B) the activity of students also increased, in the first cycle of activity studentsobtain a score of 47 (60.00%) in the category "High". While on the second cycle increasedstudent activity with a score of 52 (67.00%) to the category of "high"; and (c) the results ofsocial studies has increased, students are worth being the same as the KKM (interval 65-74)are in the first cycle there are 7 people (54.00%) and the second cycle increased by 8 votes(62.00%). To score high value (interval 75-84) in the first cycle there were 3 people (23.00%)and the second cycle there are also 3 people (23.00%). Students who reach KKM in the firstcycle there are 10 people (77.00%) and the second cycle there are 11 people (85.00%).